Prognostic Nomograms Predicting Risk of Keratoconus in Very Asymmetric Ectasia: Combined Corneal Tomographic and Biomechanical Assessments - Zhang, Xiaoyu; Ding, Lan; Sun, Ling; Huang, Yangyi; Han, Tian; Qian, Yishan; Zhou, Xingtao (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose: To develop and validate a prognostic nomogram for subclinical keratoconus diagnosis using corneal tomographic and biomechanical integration assessments. Design: Retrospective case-control study Methods: Setting: Hospital setting Patients: The study included patients with very asymmetric ectasia (VAE) and normal controls. Patients with VAE had defined clinical ectasia in one eye and normal topography (VAE-NT) in the fellow eye, and VAE-NT eyes were selected for analysis. VAE-NT was defined as stratified stage 0 using the ABCD keratoconus grading system. The normal control group was selected from corneal refractive surgery candidates at our clinic, and the right eye was enrolled. Observation Procedures: Scheimpflug-based corneal tomography (Pentacam) and corneal biomechanical assessment (Corvis ST) were performed. Main Outcome Measures: We performed multiple logistic regression analysis and constructed simple nomogram via the stepwise method. Receiver operating characteristic (ROC) curve, discrimination and calibration of prognostic nomogram were performed by 500 bootstrap resamplings to assess the determination and clinical value, respectively. Results: Fifty-nine VAE-NT and 142 normal eyes were enrolled. For differentiating normal and VAE-NT eyes, the specificity, sensitivity, area under the ROC (AUROC) was 0.7254, 0.6102, 0.7125 for tomographic parameters, 0.8857, 0.6316, 0.8109 for biomechanical parameters, and 0.8714, 0.7544, 0.8486 for combined parameters. Combined parameters showed better predictability than separated tomographic or biomechanical parameters. Conclusions: Our nomogram combined tomographic and biomechanical parameters demonstrated a plausible, capable, and widely implementable tool to predict risk of keratoconus. The identification of at-risk patients can provide advanced strategies to epitomize ectasia susceptibility.